A new genus and two new species of fossil deraeocorine plant bugs (Hemiptera: Heteroptera: Miridae) from Eocene Baltic amber - Kim, Junggon; Taszakowski, Artur; Jung, Sunghoon (Zootaxa, 2023)
A new fossil genus, Balticranocapsus gen. nov. and two new fossil species, Balticranocapsus aleksanderi sp. nov. and Deraeocoris gorczycai sp. nov. are described from Eocene Baltic amber. Morphological information, including the description and the diagnosis for the genus and species, is provided with photographs.